3D architectures of titania nanotubes and graphene with efficient nanosynergy for supercapacitors. (5th March 2017) - Ponnamma, Deepalekshmi; Vijayan P, Poornima; Al Ali Al-Maadeed, Mariam
Abstract: One dimensional titanium dioxide nanotubes (titania nanotubes or TNT) are grown on the surface of two dimensional graphene sheets by hydrothermal method so that desirable out of plane properties are obtained in the final three dimensional composite structure. The graphene oxide (GO) was first synthesized from the graphite precursor following the improved graphene oxide synthesis method and the metal oxide nanotubes, through hydrothermal method. The morphology analysis of the hybrid nanostructure illustrates the growth of nanotubes of titania on and in between the reduced GO layers and the structural details are investigated by infrared spectroscopy, X-ray photoelectron spectroscopy and Brunauer, Emmett and Teller (BET) surface area measurements. The dielectric properties illustrate the significance of this particular graphene-titania composite in fabricating supercapacitors as it exhibited a dielectric constant of 6.4 × 10 6 which is about three times more than that of the TNT. The electrochemical experiments in terms of cyclic voltammetry, Nyquist plots and charge discharge measurements further substantiate the applicability of the rationally designed nanostructure in fabricating supercapacitors. Graphical abstract: Highlights: Hydrothermal growth of TiO2 nanotubes on reduced graphene oxide sheets fabricates supercapacitors. The specific capacitance for the supercapacitor was 324 F/g. The strengthened metal oxide-graphene interface ensures 98.5% specific capacitance even after 4500 charge discharge cycles.